Implementation of e-Puskesmas in Badung District, Bali, Indonesia - I Kadek Candra Dwi Astawa Alit Putra; Ni Made Sri Nopiyani; Partha Muliawan (Public Health and Preventive Medicine Archive, 2020)
Background and purpose: Development of e-Puskesmas information system is one of the government’s efforts to improve efficiency and effectiveness of primary healthcare services. A comprehensive evaluation of e-Puskesmas implementation has not been conducted. This study aims to explore the implementation of e-Puskesmas system in Badung District from health providers’ perspectives. Methods: This study was an explorative qualitative study conducted in Badung District from July to August 2019. Datacollection was carried out through in-depth interviews with 14 informants who were selected purposively, consisted of managers and operators of e-Puskesmas in Badung District, Health Office and Public Health Centre (puskesmas). Semi-structured interview guidelines were developed based on the Health Metrics Network (HMN) Framework. Data were analyzed by thematic analysis. Data validation was carried out through source triangulation, member checking and peer debriefing. Results: The input of e-Puskesmas is generally sufficient in terms of policies, financing and infrastructure, but it is necessary to improve the quality and quantity of human resources, the internet network, and availability of standard operating procedure. The e-Puskesmas indicators have not accommodated the overall minimum health service standards of puskesmas, data on promotive and preventive programs, and data from private health care facilities. Data management is non optimal due to poor data completeness, breach of confidentiality and also the existence of other disease specific information system that is not integrated into the e-Puskesmas system. The quality of information produced from the system should be improved since there is lack of validity and unable to provide comprehensive information regarding health status of the community. The use and dissemination of information is limited to reporting to the health office while dissemination to the public has not been optimal. Conclusion: The implementation of e-Puskesmas in Badung District has not been optimal. Concerted efforts should be undertaken to overcome the barriers in the implementation and to develop a more effective, efficient and integrated health information system.